Adversity or Opportunity? Exploring the Effect of COVID-19 on Ghana’s Informal Economy - Anku-Tsede, O.; Arthur, R. (My University, 2021)
This study purported to explore the effect of the COVID-19 pandemic on the informal sector in Ghana. Particularly, the study sought to explore the nature of adversity, opportunities arising from the pandemic and remedial measures. The study adopted a mixed method and used a sample of 186 small-scale business owners and operators. The study found that the major driver of people into the informal sector were the lack of job opportunities in the formal sector rather than the need to evade government regulations. The adverse effects of the pandemic on informal businesses included lowered sales, shortage of supplies and closure of businesses. However, there were opportunities for informal businesses propelled by business diversification and technology. The study recommended the need for government to support and protect the informal sector to enhance mutual revenue generation amidst this pandemic.
Research Article
Keywords: Coronavirus; COVID-19; Informal; Economy; Africa; Ghana